2014
DOI: 10.35808/ijeba/38
|View full text |Cite
|
Sign up to set email alerts
|

Pacioli’s Innovation in Accounting: Business or Academic Affairs

Abstract: According to the accounting literature there is no evidence for earlier use of "doubleentry", as documented by Luca Pacioli in his Summa de Arithmetica Geometrica Proportioni et Proportionalita (1494), before the 13th century AD. Littleton's popular thesis links doubleentry to the increased intensity in modern times (as compared with in antiquity) of two (all inclusive) groups of economic and technical "antecedents", while Hoskin and Macve (1986) explain the articulation of double-entry in early Renaissance as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Arsentyev (2000) defines the financial security of Russia as "an essential part of economic security based on independence, efficiency, and competitiveness of the financial sector of Russia resulting in the set of measures and indicators of its state and defining the sustainability of finance, adequate assets' liquidity, and availability of monetary, currency, and gold reserves. Other researchers have defined financial security in a similar way (Ivanova et al, 2017;Kuznetsova et al, 2017;Mikhailova et al, 2017;Menshchikova and Sayapin, 2016;Kosinova et al, 2016;Sibirskaya et al, 2016;Medvedeva et al, 2015;Stroeva et al, 2015;Thalassinos and Dafnos, 2015;Duguleana and Duguleana, 2015;Kalanotnis et al, 2014;Xanthopoulos, 2014). Truntsevsky (2007) notes that financial security of the entity implies a set of conditions when corporate funds are applied in a most efficient way to prevent threats and provide the sustainable business activity from now on.…”
Section: Methodsmentioning
confidence: 99%
“…Arsentyev (2000) defines the financial security of Russia as "an essential part of economic security based on independence, efficiency, and competitiveness of the financial sector of Russia resulting in the set of measures and indicators of its state and defining the sustainability of finance, adequate assets' liquidity, and availability of monetary, currency, and gold reserves. Other researchers have defined financial security in a similar way (Ivanova et al, 2017;Kuznetsova et al, 2017;Mikhailova et al, 2017;Menshchikova and Sayapin, 2016;Kosinova et al, 2016;Sibirskaya et al, 2016;Medvedeva et al, 2015;Stroeva et al, 2015;Thalassinos and Dafnos, 2015;Duguleana and Duguleana, 2015;Kalanotnis et al, 2014;Xanthopoulos, 2014). Truntsevsky (2007) notes that financial security of the entity implies a set of conditions when corporate funds are applied in a most efficient way to prevent threats and provide the sustainable business activity from now on.…”
Section: Methodsmentioning
confidence: 99%
“…The father of modern accounting is Italian Luca Pacioli, who in 1494 first described the system of double-entry bookkeeping used by Venetian merchants in his Summa de Arithmetica, Geometria, Proportioni et Proportionalita. While he was not the inventor of accounting, Pacioli was the first to describe the system of debits and credits in journals and ledgers that is still the basis of today's accounting systems (Kalantonis et al, 2014). The growth of Accountancy contributed decisively in the profitability and in the wealth of enterprises during the Italian art movement via which was supported and was elected the cultural blossoming that was marked at the 16th-century High Renaissance, with the financing of excellent and unique work of art and the featuring of leading authors, artists and scientists (Gleeson-White, 2013).…”
Section: The Storymentioning
confidence: 99%
“…Besides, several writers make their connection of the pedagogues' influence upon accounting in early Renaissance through "new textuality" the internal re-writing of the text into accounts and the double writing of money, which would later eventuate into double-entry and after the process was taken farthest by those who dealt most fully with the sophisticated money instruments" (Hoskin and Macve, 1986: 114 and 120). From the new textuality technique, new accounting systems for recording purposes and accounts keeping, are eventually developing or supporting such systematic examinations of incoming written statements (Kalantonis et al, 2014). From the analysis of this research it is found that the "Accounting" application in the registration of financial transactions is mainly limited to the single-entry method and is inspired by the need to "arrange" the financial and consequently accounting transactions.…”
mentioning
confidence: 99%
“…Statements prepared according to the international financial reporting standards (IFRS) should meet very high requirements associated with the transparency of information. The statements complying with the IFRS provides a more accurate outlook on the financial status of the company, its changes and the results of the group's work, as well as they ensure a greater independence in decision-making (Theriou, 2015;Tsamis andLiapis, 2014, Theriou andAggelidis, 2014;Hapsoro and Suryanto, 2017;Kalanotnis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%